Metagenomic analysis of intestinal microbiota in geese from different farming systems in Gunungpati, Semarang - R Susanti; Ari Yuniastuti; Fitri Arum Sasi; Muchamad Dafip (Indonesian Journal of Biotechnology, 2020)
The diversity of intestinal bacteria in geese correlates with environmental conditions, rearing methods, and consumed feeds. The intestinal bacteria composition is useful for the absorption of nutrition, improving the metabolism, and may be related to the immune system. This study was conducted to examine the intestinal bacteria composition and the diversity of maintained goose in aviaries and barns. This research was an observational exploratory. Five geese were taken purposively from local breeders in Gunungpati District, Semarang City. A total of 5 g of intestinal contents from each sample was used for microbial genome isolation. Then, the genome was amplified to collect 16S rRNA gene region V3-V4. The amplicons were then sequenced using the next generation sequencing (NGS) method (Illumina high-throughput sequencing; paired-end reads) and analyzed using QIIME2 to identify bacterial species. In addition, GC-MS was performed to identify and measure fatty acid contents in the intestinal. The results showed that both rearing and caged goose contained nine phyla of intestinal bacteria. The number of intestinal bacteria of barn geese (SU) reached 32,748 Operational Taxonomy Units (OTU); higher than aviary geese (SK), which was 11,646 OTU. The intestinal bacteria community in barn geese was approved by Phylum TM7 (Saccharibacteria candidate) (53.18%), followed by Firmicutes (32.51%) and Bacteriodetes (5.42%). Whereas on SK Firmicutes was compiled 49.3 4% of total OTU, TM7 (S. candidate) up to 21.17%, and Actinobacteria up to 15.99 %. The abundance of TM7 may contribute to high 9,12-octadecadienoic acid production, while Firmicutes was related to the high production of oleic acid. Based on these data, the reared geese had a more abundant diversity of bacteria than the caged one.